Democracy Education As A Vehicle to Anticipate the Development of SARA Politics in Elections - Muhammad Hendri Nuryadi; Pipit Widiatmaka (Jurnal Paedagogy, 2024)
This study aims to determine the role of democratic education in anticipating racial politics and the implications of democratic education on harmony between differences. This study used a qualitative approach with a literature research method. The data collection technique in this research was documentation (journals articles (nationally reputable, nationally indexed by Sinta, internationally indexed by DOAJ, and internationally indexed by Scopus), books, online news and others) and the data analysis used is content analysis. The results showed that the role of democratic education is to instill democratic values based on the nation's personality, such as tolerance, responsibility, openness between others, justice, realizing diversity, humanity and others. Democracy education activities could be carried out in schools through civic education learning, in the family environment carried out by often interacting with friends or relatives who have differences in religion, ethnicity, race and others, and in the community can be done by deliberation in RT meetings and holding regional art activities. Governments, political parties, organizations, and families can organize democracy education. Suppose the role of democracy education runs optimally. In that case, it can anticipate politics with SARA nuances so that it will have implications for harmony between others, including religions, tribes, races, groups and so on. Harmony of life among others in the life of the nation and state is the ultimate goal of democratic education.